How is Military Chaplaincy in Europe Portrayed in European Scientific Journal Articles between 2000 and 2019? A Multidisciplinary Review - Tiia Liuski; Martin Ubani (Religions, 2020)
This article focuses on the portrayal of the military chaplaincy in Europe in European scientific journal articles during the past two decades. The military chaplaincy represents an interesting case as it is a member of two strong professions: a soldier and the clergy. Furthermore, the profession is facing many challenges connected to diversification and pluralisation, networking, technology, and extraprofessional collaboration. The data of the review study included scientific journal articles that are published electronically in major scientific databases. When portraying military chaplaincy, the articles emphasised five themes: Basic functions, the history of the profession, the changing nature of the military chaplaincy, organisational change, and professional ethics.